Longitudinal pathways between perceived oral health and regular service use of adult Finns - Torppa-Saarinen E.; Suominen A.; Lahti S.; Tolvanen M. (Blackwell Munksgaard, 2022)
Objectives: Our aim was to evaluate changes in and pathways between different measures of perceived oral health (POH) and regular oral health service use between the years 2000 and 2011 among Finnish adults. POH was measured by means of oral health‐related quality of life (OHRQoL) and subjective oral health (SOH).
Methods: The study was based on a longitudinal sample (n = 5525) of adults having participated both in the Health 2000 and 2011 Surveys (BRIF 8901). OHRQoL was measured with the Oral Health Impact Profile 14‐item questionnaire and SOH with a single question. Path analyses were used to determine whether SOH or OHRQoL affected service use or vice versa, grouped by age groups and self‐assessed treatment need.
Results: The path analyses indicate that good OHRQoL leads to regular service use and regular service use leads to better SOH. The first path was stronger among the elderly (0.10) and the second among the younger age group (0.07). Both paths were stronger (0.12 and 0.06) among those who reported no treatment need in 2000.
Conclusions: Good OHRQoL, indicated by a lack of perceived problems or symptoms, leads to regular service use. Our findings indicate that poor OHRQoL leads to nonregular service use, and nonregular service use leads to poor SOH.